PERKAWINAN ADAT WANGKUNG RAHONG DALAM PERSPEKTIF PERKAWINAN GEREJA KATOLIK (PERBANDINGAN PANDANGAN, TUJUAN DAN SIFAT PERKAWINAN) - Mbukut, Antonius (Jurnal Masalah Pastoral, 2023)
This paper will explain the concept of traditional marriage of the people of Wangkung Rahong (a village in Manggarai) which includes the views, purpose and nature of marriage and will further be reflected in the context of the marriage of the Catholic Church. The author would like to compare with looking for and find similarities and differences between the views, purpose, and nature of traditional marriage of Wangkung Rahong people with the concept of marriage of the Chatolic Church. After finding the similarities and differences in views, purpose and nature, the author will reveal the pastoral implications of the similarities and differences in views, purpose and nature of Wangkung Rahong traditional marriage with the Catholic Church marriage.